Para‐Functionalization of N‐Substituted 4‐amino[2.2]paracyclophanes by Regioselective Formylation. Issue 29 (20th April 2021) - Felder, Simon; Micouin, Laurent; Benedetti, Erica
Abstract: Herein, we report a simple and convenient procedure to prepare para ‐disubstituted [2.2]paracyclophanes in a straightforward manner. Our approach relies on a regioselective formylation of N‐substituted 4‐amino[2.2]paracyclophanes, which allows an easy access to a series of products incorporating a reactive aldehyde function para to the electron‐donating group. These compounds can be engaged in a variety of orthogonal late‐stage derivatization processes involving either the carbonyl group or the amine function, and can serve as precursors to rapidly access more complex paracyclophane derivatives. Control of planar chirality is also possible by performing a kinetic resolution of key racemic intermediates through asymmetric transfer hydrogenation. The formylation can be run on a synthetically useful scale, thus confirming the practical applicability of our method. Abstract : A regioselective formylation of N‐substituted 4‐amino[2.2]paracyclophanes is described, which allows an easy access to key synthetic intermediates which are useful for the preparation of a large variety of para di‐substituted paracyclophanes in a straightforward manner.